Ecogeography, demography, diversity and conservation of Phaseolus lunatus L. in the Central Valley of Costa Rica - Baudoin, Jean-Pierre; Rocha, O.; Degreef, J.; Maquet, A.; Guarino, Luigi (2004)
Much has been said about the need to base biodiversity conservation strategies on solid scientific foundations, for example in international agreements such as the Convention on Biological Diversity and The State of the World's Plant Genetic Resources for Food and Agriculture. Of course, this requires data, often in large amounts. The task of collating and analyzing these data is a complex, expensive and time-consuming exercise, especially where wild species are concerned, requiring expertise in a number of disparate technical fields. This publication summarizes the results of an IPGRI project ('Studies on breeding systems: the case of a short-living perennial, alternatively outbreeder-inbreeder species - Phaseolus lunatus L. - and its consequences for germplasm conservation') which systematically gathered detailed ecogeographic, demographic, phenological and genetic data, and used these to develop and implement an effective, sustainable conservation strategy for a wild relative of a crop plant. Wild and weedy relatives of cultigens are an extremely important source of genes for crop improvement, but these crucial genetic resources are coming under increasing pressure the whole world over, as wild habitats are altered, degraded and lost. Although wild Lima bean in the Central Valley of Costa Rica was the specific focus of the project, the approaches and tools used to analyze and apply the extensive and varied data that were amassed will be widely applicable. These are important achievements, and are a testament to the dedication of the project partners, the Escuela de Biología of the Universidad de Costa Rica (UCR) and the Unité de Phytotechnie Tropicale et d'Horticulture of the Faculté Universitaire des Sciences Agronomiques de Gembloux (FUSAGx), Belgium. They also illustrate the far-sightedness of the donor, Belgium's Direction Générale de la Coopération au Développement, which has supported the project over two phases lasting 8 years. IPGRI, and in particular its Regional Office for the Americas in Cali, Colombia, is proud to have initiated this project and to have been involved in its implementation as the coordinating institution. We look forward to, and will work towards, the wide dissemination of its results and their application to the conservation of biodiversity, and in particular wild relatives, in other parts of the world.